O talking back da “negra africana”: o ser desencarnado e silenciado da empregada doméstica Janair em A paixão segundo G.H. - Pires, Francisco (Brasiliana: Journal for Brazilian Studies, 2019)
In Clarice Lispector’s A paixão segundo G.H., the character Janair is a black maid who becomes a remarkable presence precisely because of her physical absence. The character G.H., narrator of the book and Janair’s former employer, expresses an eloquent silence about this Afro-Brazilian character, defining Janair as “an black African woman” and stressing her struggle to connect with Janair: “I shuddered when I finally realized that this woman was an invisible”. Due to a discriminatory process that derives from the intersection of race, class and gender, Janair occupies the space socially marked by invisibility. In Lispector’s book, the maid seems to come from another reality, looming metaphorically as a foreign, relegated, disembodied figure.